VD_FINDINFO Décision / 2014 / 201 vom 7. Januar 2014 - VD Tribunal cantonal (2014)
PLAIGNANT, LÉSÉ, MORT, PARENTS, ASSISTANCE JUDICIAIRE, PARTIE À LA PROCÉDURE | 104 CPP (CH), 115 al. 1 CPP (CH), 116 al. 2 CPP (CH), 117 CPP (CH), 118 al. 1 CPP (CH), 121 al. 1 CPP (CH), 136 CPP (CH), 393 CPP (CH)